Long‐term prognostic value of the FibroTest in patients with non‐alcoholic fatty liver disease, compared to chronic hepatitis C, B, and alcoholic liver disease. Issue 10 (17th October 2018) - Munteanu, Mona; Pais, Raluca; Peta, Valentina; Deckmyn, Olivier; Moussalli, Joseph; Ngo, Yen; Rudler, Marika; Lebray, Pascal; Charlotte, Frederic; Thibault, Vincent; Lucidarme, Olivier; Ngo, An; et al.
Summary: Background: Although the FibroTest has been validated as a biomarker to determine the stage of fibrosis in non‐alcoholic fatty liver disease (NAFLD) with results similar to those in chronic hepatitis C (CHC), B (CHB), and alcoholic liver disease (ALD), it has not yet been confirmed for the prediction of liver‐related death. Aim: To validate the 10‐year prognostic value of FibroTest in NAFLD for the prediction of liver‐related death. Method: Patients in the prospective FibroFrance cohort who underwent a FibroTest between 1997 and 2012 were pre‐included. Mortality status was obtained from physicians, hospitals or the national register. Survival analyses were based on univariate (Kaplan‐Meier, log rank, AUROC) and multivariate Cox risk ratio taking into account age, sex and response to anti‐viral treatment as covariates. The comparator was the performance of the FibroTest in CHC, the most validated population. Results: 7082 patients were included; 1079, 3449, 2051, and 503 with NAFLD, CHC, CHB, and ALD, respectively. Median (range) follow‐up was 6.0 years (0.1‐19.3). Ten year survival (95% CI) without liver‐related death in patients with NAFLD was 0.956 (0.940‐0.971; 38 events) and 0.832 (0.818‐0.847; 226 events; P = 0.004) in CHC. The prognostic value (AUROC / Cox risk ratio) of FibroTest in patients with NAFLD was 0.941 (0.905‐0.978)/1638 (342‐7839) and even higher than in patients with CHC 0.875 (0.849‐0.901; P = 0.01)/2657 (993‐6586). Conclusions: The FibroTest has a high prognostic value in NAFLD for the prediction of liver‐related death. (ClinicalTrials.gov number, NCT01927133).